Examining the exisiting provisions and regulation on matrimonial asset involving matrimonial home - Sahari, Noorul Huda; Mohd Zin, Najibah; Abd Manan, Siti Khadijah; Saidon, Rafeah; Mohd Daud, Norzaidi (International Digital Organization for Scientific Information (IDOSI), 2014)
This paper aimed to examine the existing provisions and regulation with regards distribution of matrimonial asset involving matrimonial home. The study adopted a qualitative method and the samples were collected from six zones representing Shariah Courts in Malaysia. The findings show that the rigidity in the provision cause inconsistency in the practice of the court where the court cannot fully comply with the existing proportion in the stated provision. The transfer of matrimonial home to the divorced wife is among the agreed division achieved in sulh and it is considered a practical approach in protecting the interest of the wife and children for support after divorce. This study is perhaps the first that concentrate on matrimonial asset involving matrimonial home.